The role of SQSTM1/P62 in axonal development and degeneration in an ALS-FTLD context - Young, Matthew J. (2020)
Amyotrophic lateral sclerosis and associated frontotemporal lobe dementia (ALS- FTLD) is a complex, fatal degenerative disease encompassing selective degeneration of upper and lower motor neurons, as well as neurons of the frontal and temporal brain regions, resulting in neuromuscular failure and dementia-like cognitive defects. In ALS-FTLD, disease progression is often rapid, with no effective cures currently available.